2012
DOI: 10.1111/j.1365-3059.2012.02613.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic evidence that basidiospores play an important role in the disease cycle of rice‐infecting populations of Rhizoctonia solani AG‐1 IA in Iran

Abstract: The fungus Rhizoctonia solani AG-1 IA causes sheath blight, one of the most important rice diseases worldwide. The first objective of this study was to analyse the genetic structure of R. solani AG-1 IA populations from three locations in the Iranian Caspian Sea rice agroecosystem. Three population samples of R. solani AG-1 IA isolates were obtained in 2006 from infected rice fields separated by 126-263 km. Each field was sampled twice during the season: at the early booting stage and 45 days later at the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…The evidence for recombination (most of the loci in HWE and gametic disequilibrium) was found in all three country populations, indicating that the sexual cycle likely occurs on rice in China, Japan and the Philippines and thus, basidiospores may play an important role in the epidemiology of the sheath blight, despite the fact that they are considered not easily detectable in nature. This finding is consistent with earlier studies of rice infecting populations from India (Linde et al, 2005), USA (Rosewich et al, 1999) and Iran (Padasht-Dehkaei et al, 2010) showing a mixed reproductive system of the fungus. The mixed reproductive system of pathogens such as R. solani AG-1 IA, that combines sexual and asexual reproduction, may facilitate the rapid emergence of host specialization, virulence and fungicide resistance (Milgroom, 1996;McDonald & Linde, 2002).…”
Section: Fungal Reproductive System: Genotypic Diversity Clonal Fracsupporting
confidence: 93%
See 1 more Smart Citation
“…The evidence for recombination (most of the loci in HWE and gametic disequilibrium) was found in all three country populations, indicating that the sexual cycle likely occurs on rice in China, Japan and the Philippines and thus, basidiospores may play an important role in the epidemiology of the sheath blight, despite the fact that they are considered not easily detectable in nature. This finding is consistent with earlier studies of rice infecting populations from India (Linde et al, 2005), USA (Rosewich et al, 1999) and Iran (Padasht-Dehkaei et al, 2010) showing a mixed reproductive system of the fungus. The mixed reproductive system of pathogens such as R. solani AG-1 IA, that combines sexual and asexual reproduction, may facilitate the rapid emergence of host specialization, virulence and fungicide resistance (Milgroom, 1996;McDonald & Linde, 2002).…”
Section: Fungal Reproductive System: Genotypic Diversity Clonal Fracsupporting
confidence: 93%
“…This is because the role of basidiospores in the fungal disease cycle is not yet fully understood (Rosewich et al, 1999;Bernardes de Assis et al, 2009). However, strong evidence that basidiospores can be an important source of inoculum shaping the genetic structure of the fungal populations towards a mixed reproductive system has been reported in Iran, in the Middle East (Padasht-Dehkaei et al, 2010). In addition, basidiospores of R. solani AG-1 IA have been commonly detected in Asia, in Japanese rice paddy fields (Miyasaka & Nakajima, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Other isolates of R. solani AG1‐IB, AG1‐IC and R. oryzae‐sativae have been associated with sheath blight symptoms to a lesser extent (Taheri et al ., ; Chaijuckam et al ., ). Rhizoctonia solani AG1‐IA can cause many diseases such as sheath blight and sheath spot on rice, banded leaf and sheath blight on maize, aerial blight and stem blight on soybean, mungbean and cowpea, sheath blight on sorghum, and foliar blight on durian and coffee (Padasht‐Dehkaei et al ., ). It was thought to be mainly an asexual fungus on rice, although sexual structures from its teleomorph have occasionally been observed in fields (Chaijuckam et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Knowledge of the genetic structure of pathogen populations is essential to elucidate their life histories and the evolutionary potential in agricultural ecosystems (McDonald & Linde, ). The genetic structure of R. solani populations has been studied using different molecular markers, such as randomly amplified polymorphic DNA (RAPD) markers (Singh et al ., ; Wang et al ., ), restriction fragment length polymorphism (RFLP; Rosewich et al ., ), analysis of sequence variation in ribosomal DNA (rDNA) and β ‐tubulin genes (Fenille et al ., ; Ceresini et al ., ), inter‐simple sequence repeats (ISSR; Guleria et al ., ); amplified fragment length polymorphism (AFLP; Taheri et al ., ), single nucleotide polymorphisms (SNPs; Ciampi et al ., ) and simple sequence repeats (SSR; González‐Vera et al ., ; Padasht‐Dehkaei et al ., ). Many studies have shown that there is a high level of genetic variability in R. solani populations, and that several AGs possess homothallic and heterothallic mating systems.…”
Section: Introductionmentioning
confidence: 97%
“…The pots incubated in a greenhouse conditions (16 h light and 8 h dark cycle). Pure culture of R. solani AG1-IA isolate G88, highly virulent isolate known from Iran (Padasht-Dehkaei et al 2013), was prepared by transferring of fungal sclerotia to 9 cm petri dishes containing potato dextrose agar (PDA). 60-day-old plants were inoculated with 5 mm agar discs of R. solani culture.…”
Section: Rhiz − Pita Gene Expression Alteration In Infected Rice Plantsmentioning
confidence: 99%